1998
DOI: 10.1021/ma971072m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Hindered Polyphosphazenes via Functionalized Intermediates: Exploratory Models for Electro-optical Materials

Abstract: Several cosubstituent polyphosphazenes were synthesized that incorporate the nonlinear optical chromophore, disperse red 1 (DR-1), linked covalently to the polymer backbone through spacer groups. These polymers have a high chromophore loading (one DR-1 per repeat unit), have glass transition temperatures near 100 °C, and are high refractive index materials (n = ∼1.71). The syntheses were achieved via unconventional reactions that involve functionalized poly(organophosphazenes). Disperse red-1 was linked to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Most polyphosphazenes have very high molecular weight, and they are usually amorphous, soluble, and easily prepared 1–4. Because of these advantages, they were considered as an excellent candidate for electrooptical (EO) applications 5–7. In 1991, a second‐order nonlinear optical (NLO) chromophore, dispersed red‐1 (DR‐1), was first linked to the phosphorus–nitrogen backbone by Allcock et al5 to synthesize new NLO polymeric materials; the resultant polyphosphazenes showed good properties such as stability and processibilty and demonstrated that polyphosphazenes might be promising polymeric materials for the NLO applications, except that T g was only 58°C.…”
Section: Introductionmentioning
confidence: 99%
“…Most polyphosphazenes have very high molecular weight, and they are usually amorphous, soluble, and easily prepared 1–4. Because of these advantages, they were considered as an excellent candidate for electrooptical (EO) applications 5–7. In 1991, a second‐order nonlinear optical (NLO) chromophore, dispersed red‐1 (DR‐1), was first linked to the phosphorus–nitrogen backbone by Allcock et al5 to synthesize new NLO polymeric materials; the resultant polyphosphazenes showed good properties such as stability and processibilty and demonstrated that polyphosphazenes might be promising polymeric materials for the NLO applications, except that T g was only 58°C.…”
Section: Introductionmentioning
confidence: 99%
“…The schematic for the reaction pathway is shown in Scheme 1. (It should be noted that Allcock et al [34] employed a similar procedure to couple the DR1 chromophore to hydroxyl-functionalized polymers, with the hydroxyl units attached to phenyl rings, and achieved 100% coupling efficiency). Excess untethered DR1-TS was extracted by repeated flushing of the copolymer product with methylene chloride during a final filtering process until the methylene chloride being outputted from the filtering apparatus was clear for substantial time.…”
Section: Synthesismentioning
confidence: 99%
“…They present a number of useful features for practical devices, such as the excellent flexibility of the backbone, high thermal and oxidative stability, optical transparency from 220 nm to the near-IR region, and controlled covalent incorporation of chromophores can be easily accomplished over a broad concentration range. Recently, some new synthetic routes [20][21][22][23][24][25][26] have been developed for the preparation of polyphosphazenes with large molecular hyperpolarizabilities and high glass-transition temperatures.…”
Section: Introductionmentioning
confidence: 99%